Analysis Of Transhumanism In The Cultural And Religious Context - Suvonova Umida Amriddin qizi (Zien Journals, 2024)
This paper explores the concept of transhumanism within a cultural and religious framework, examining how advancements in technology intersect with traditional beliefs and cultural practices. Transhumanism, which seeks to enhance human capabilities through technological means, raises significant questions regarding its compatibility with cultural and religious values. The paper investigates whether the goals of transhumanism align with or challenge the moral, ethical, and spiritual aspects of various religious and cultural ideologies. By analyzing different perspectives, the research highlights the potential conflicts, challenges, and opportunities that arise when transhumanism is applied in cultural and religious contexts. The study also considers the implications of transhumanist advancements on the future of humanity from a philosophical standpoint, emphasizing the importance of balancing technological progress with respect for human dignity and cultural identity
Keywords: transhumanism; cultural context; religious beliefs; technology